Management of Full Day School Program in Improving School Quality - Agus Riyanto; Asdlori Asdlori; Abu Dharin; Slamet Pamuji (Universitas Nurul Jadid, 2025)
This study examines the management of the full day school program and its contribution to improving school quality. The research responds to the growing demand for educational models that integrate academic achievement with character development within extended learning systems. A qualitative case study approach was employed to explore managerial practices, stakeholder roles, and institutional dynamics. Data were collected through in-depth interviews, field-based insights, and document analysis, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the effectiveness of the full day school program is closely linked to the integration of four key managerial functions: planning, organizing, implementation, and evaluation. Planning is conducted collaboratively by integrating the national curriculum with Islamic character education. Organizational practices involve clear role distribution and coordinated responsibilities among school personnel. The implementation phase reflects a holistic learning model that combines academic instruction, Qur’anic memorization, leadership training, and extracurricular activities. Evaluation is carried out through academic assessments, internal reflection, and parental feedback, ensuring continuous improvement. The study highlights that successful full day school management contributes not only to academic achievement but also to character formation and institutional credibility. These findings emphasize the importance of adaptive and value-based management in enhancing educational quality, particularly within the context of Islamic educational institutions.